Performance Comparison of NGINX, Apache, and Lighttpd Using WRK on a Debian - Wahyu Wicoksono; Herman Azzra Mustaqhim; Panchadria Pramana Anwas; Laela Neng Linda Badratul (bit-Tech, 2025)
A web server plays a crucial role in delivering HTTP-based services that are essential for web applications and information systems. In environments with limited resources, such as Virtual Private Servers (VPS), selecting the most efficient web server becomes a key consideration to ensure system stability and responsiveness. This study addresses the performance comparison of three widely used web servers—Apache, NGINX, and Lighttpd—under various load conditions, with the aim of identifying which server provides the best performance in constrained environments. The experimental method was applied using the WRK benchmarking tool, which simulates concurrent user connections under four scenarios combining different user counts (50 and 100 users) and durations (1 and 3 seconds). The performance metrics evaluated include latency, requests per second (RPS), and transfer rate. Results showed that Apache consistently offered the best overall performance with low latency and high RPS, making it a reliable and stable option. NGINX demonstrated strong performance in handling concurrent connections and showed the highest transfer rate, although it requires more complex configuration. Lighttpd, while lightweight and efficient in resource usage, exhibited weaker performance in high-load scenarios. This research contributes to the current body of literature by offering up-to-date and practical benchmarking data. The findings serve as a useful reference for developers and system administrators in selecting a web server based on specific operational needs, resource availability, and performance priorities in modern VPS-based infrastructures.